2020
DOI: 10.3390/ani10122279
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Avocado and Mango Fruit Wastes in Multi-Nutrient Blocks for Goats Feeding: In Vitro Evaluation

Abstract: This study was conducted to investigate the nutritive value of avocado and mango fruit wastes, and to assess the possibility of preserving the wastes into multi-nutrient blocks (MB). Both peels and a pulp:peels (PP) mixture of each fruit were analyzed for chemical composition and in vitro fermentation with goats’ ruminal fluid. Wastes had low-dry matter (DM) content (<250 g/kg), with those from mango having high non-structural carbohydrates content (>800 g/kg DM) and those from avocado high fat levels (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…More specifically, it has been found that pomegranate peel contains saponins that can improve nitrogen efficiency by reducing the activity of protozoa [ 27 ], enhancing the microbial composition of stomach proteins and increasing the protein content of the produced milk. Similar results have been commented by [ 30 , 31 , 32 ] who studied the effect of a combination of pomegranate, flaxseed seed oil, avocado, and mango fruit wastes, respectively, on the effect of daily milk production of goats, as well as blood, containing metabolites and their antioxidant status. Recent studies also investigated the effect of incorporating pomegranate by-products in the diet of lambs [ 33 ] and cows [ 34 ], while [ 35 ] commented avocado use as potential feedstuff for animals as an energy source.…”
Section: Introductionsupporting
confidence: 85%
“…More specifically, it has been found that pomegranate peel contains saponins that can improve nitrogen efficiency by reducing the activity of protozoa [ 27 ], enhancing the microbial composition of stomach proteins and increasing the protein content of the produced milk. Similar results have been commented by [ 30 , 31 , 32 ] who studied the effect of a combination of pomegranate, flaxseed seed oil, avocado, and mango fruit wastes, respectively, on the effect of daily milk production of goats, as well as blood, containing metabolites and their antioxidant status. Recent studies also investigated the effect of incorporating pomegranate by-products in the diet of lambs [ 33 ] and cows [ 34 ], while [ 35 ] commented avocado use as potential feedstuff for animals as an energy source.…”
Section: Introductionsupporting
confidence: 85%
“…Furthermore, PE increased the concentration of ruminal NH 3 -N, which might be due to the role of PE in enhancing the proteolysis process. This nitrogen source can be captured and used by rumen microorganisms to build their own protein [ 27 ], which in turn would be used as a protein source for the animal [ 28 ]. A similar effect has been reported when this PE was used as a feed supplement with a 70:30 ratio of forage to concentrate diet in the rumen simulation technique (RUSITEC) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…NB can partially replace concentrates in the dietary ration. Carlos et al [81] examined in vitro fermentation of avocado and mango wastes (peels and a pulp:peels (PP) mixture) with goat rumen fluid and the potential of including the PP mixture in NB for goats. The wastes had high moisture content, high levels of non-structural carbohydrates from mango and high levels of fat from avocado.…”
Section: Lick Blocks Can Partially Replace Concentratesmentioning
confidence: 99%